THE PROFILE OF DIABETIC FOOT PATIENTS MORTALITY IN THE SURGICAL WARDS - Sultan Hussain Ahmed Daghasi; Ayoub Bnider Habib Almokheldi; Hassan Abdel Hadi Gomaa Shawoush; Abdulaziz Saleh Saudi Sharbah; Hamed said Ali Alshamrani; Ahmed Maadi Mohammed Al-Rafidi (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Diabetic foot patients in surgical wards face higher risk of mortality due to the complications associated with the disease. This comprehensive study aims to analyze the profile of diabetic foot patients in surgical wards who succumb to mortality. Results indicate that age, comorbidities, and wound severity play significant roles in predicting mortality in these patients. The discussion highlights the importance of multidisciplinary teamwork and comprehensive care in mitigating mortality rates. Ultimately, this research underscores the need for further studies and interventions to improve outcomes for diabetic foot patients in surgical wards.